2000
DOI: 10.1073/pnas.97.2.565
|View full text |Cite
|
Sign up to set email alerts
|

Highly mutagenic replication by DNA polymerase V (UmuC) provides a mechanistic basis for SOS untargeted mutagenesis

Abstract: When challenged by DNA-damaging agents, Escherichia coli cells respond by inducing the SOS stress response, which leads to an increase in mutation frequency by two mechanisms: translesion replication, a process that causes mutations because of misinsertion opposite the lesions, and an inducible mutator activity, which acts at undamaged sites. Here we report that DNA polymerase V (pol V; UmuC), which previously has been shown to be a lesionbypass DNA polymerase, was highly mutagenic during in vitro gap-filling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
95
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 51 publications
5
95
1
1
Order By: Relevance
“…UmuDЈ does not act in the DNA damage checkpoint control, but rather participates in the second role of the umuDC gene products. The UmuDЈ 2 homodimer interacts with UmuC, forming the UmuDЈ 2 C complex (pol V), that functions as a lesion-bypass DNA polymerase to enable translesion DNA synthesis (TLS) (11,12,23,24). Viewed in this way, posttranslational modification of UmuD to yield UmuDЈ acts as a molecular switch to regulate temporally the two physiological roles of the umuDC gene products.…”
mentioning
confidence: 99%
“…UmuDЈ does not act in the DNA damage checkpoint control, but rather participates in the second role of the umuDC gene products. The UmuDЈ 2 homodimer interacts with UmuC, forming the UmuDЈ 2 C complex (pol V), that functions as a lesion-bypass DNA polymerase to enable translesion DNA synthesis (TLS) (11,12,23,24). Viewed in this way, posttranslational modification of UmuD to yield UmuDЈ acts as a molecular switch to regulate temporally the two physiological roles of the umuDC gene products.…”
mentioning
confidence: 99%
“…This stalling provides an entry point for the constitutively present SOS proteins, leading to increased probability of mismatch extension and, hence, mutation. In view of the recent discovery of a polymerase activity for UmuC or UmuD 2 C (pol V) (3)(4)(5)(6), it is likely that this polymerase is responsible for the mismatch extension. However, the exact chain of events leading to mismatch extension, including the precise exchange and interplay between pol III and pol V, remains to be elucidated.…”
mentioning
confidence: 99%
“…The UmuDЈ 2 C complex then acts jointly with RecA protein, which also has a direct role in the process, to create mutations at the sites of DNA lesions (targeted mutagenesis). The UmuDЈ 2 C complex has recently been demonstrated to possess a polymerase activity (pol V) (3)(4)(5)(6), which likely plays a critical role in producing the mutation. UmuC is an example of a specialized polymerase, a number of which have been reported from a variety of organisms and which are generally thought to function in mutagenesis and DNA damage processing (for reviews, see refs.…”
mentioning
confidence: 99%
“…This protein complexes with UmuDЈ protein (a proteolytically processed form of UmuD) to form a UmuDЈ 2 C complex that facilitates TLS in the presence of E. coli DNA polymerase III holoenzyme (1)(2)(3)(4)(5)13). The UmuDЈ 2 C complex alone (most likely the UmuC polypeptide) is now called DNA polymerase V of E. coli (16)(17)(18). More recent studies have shown that DNA polymerase V bypasses thymine-thymine dimers, photoproducts, and abasic sites in a highly error-prone manner in vitro (19).…”
mentioning
confidence: 99%